2016
DOI: 10.1136/bcr-2016-216965
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Cushing syndrome with detectable ACTH from an unexpected source

Abstract: Mixed corticomedullary adrenal tumours (MCMT) are rare. We describe the second reported case of a male patient presenting with hypertension and Cushing syndrome with MCMT. A man aged 48 years presented with hypertension and signs of Cushing syndrome. 24-hour urine cortisol was elevated, with detectable adrenocorticotropic hormone (ACTH). A high-dose dexamethasone suppression test indicated an adrenal or ectopic Cushing syndrome. Plasma metanephrines were normal. A 3 cm left adrenal mass was identified without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Four cases were found in other languages (Chinese, Japanese, Korean, and Russian); these were not included in our study [ 54–57 ]. Other mechanisms for the development of ectopic Cushing syndrome from a pheochromocytoma have been reported, such as corticotropin-releasing hormone secretion [ 58–60 ] or mixed corticomedullary tumors [ 61 , 62 ]. Other cases have been reported as part of the MEN 2A syndrome with bilateral masses [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four cases were found in other languages (Chinese, Japanese, Korean, and Russian); these were not included in our study [ 54–57 ]. Other mechanisms for the development of ectopic Cushing syndrome from a pheochromocytoma have been reported, such as corticotropin-releasing hormone secretion [ 58–60 ] or mixed corticomedullary tumors [ 61 , 62 ]. Other cases have been reported as part of the MEN 2A syndrome with bilateral masses [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…As conceptualized in an old study, steroidogenic precursors (21-deoxycortisol) secreted by ACC may antagonize the glucocorticoid feedback at the hypothalmic-pituitary level [36,37]. Although the intra-adrenal source of ACTH has been reported in PBMAH and mixed cortico-medullary adrenal tumors (MCMT), the evidence to support the production of ACTH or ACTH-like substances from ACC is negligible [38,39]. The evaluation for the possible role of heterophile antibodies was not performed in our study.…”
Section: Discussionmentioning
confidence: 83%
“…Further, adrenocortical cells produced cortisol in most cases and aldosterone in two cases, and only one case produced dehydroepiandrosterone sulfate (DHEA-sulfate). Seven of 12 previous cases with elevated cortisol had unsuppressed ACTH levels, despite a hypercortisolemic state (19). The detectable ACTH level was not grossly elevated, as is usually seen from pituitary or ectopic sources (19).…”
Section: Clinical Manifestations and Laboratory Findingsmentioning
confidence: 83%
“…The detectable ACTH level was not grossly elevated, as is usually seen from pituitary or ectopic sources (19). We added six subsequent cases from the reports after Lwin et al (19) and found that 71% (10/14) of MCMTs had subclinical Cushing syndrome with ectopic ACTH. In cases with Cushing syndrome, ectopic ACTH syndrome was defined as ACTH dependent when the plasma ACTH level was >15 pg/ml (reference range: 10-50 pg/ml) and ACTH independent when the plasma ACTH level was <5 pg/ml based on a previous report (23).…”
Section: Clinical Manifestations and Laboratory Findingsmentioning
confidence: 93%
See 1 more Smart Citation